Typology of Mixed Sheep and Goat Production System in the Regional Unit of Larissa, Greece - Kaimakamis, I; Dotas, V; Gourdouvelis, D; Chatzizisis, L; Koidou, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The study was carried out using a structured questionnaire in 162 sheep and goat farms of mixed production system in the Regional Unit of Larissa during February 2020 - February 2021. The Hierarchical Cluster Analysis application has shown three basic production systems. Cluster 1 consists of medium size holdings (233.02 livestock units), which earn additional income from other activities. Cluster 2 consists of rather large size farms (1,825.66 livestock units) with a net profit per female 2.61 euros. This type of farms breed livestock based on the semi-intensive and intensive production system, have large rented areas for the cultivation of feed, while the contribution of subsidies is especially high to the shaping of their gross income. The largest percentage (59.88%) of the holdings falls under the third cluster. These are specialized types of livestock farming, which present the largest net profit per livestock animal. 4% of this type of holdings breeds animals based on the semi-nomadic system while 100% uses common pastures as feed source.